Corporate Social Responsibility as Core Competence for the Business Model of Social Start-Ups in the Netherlands - Wevers, Herman T.; Voinea, Cosmina L. (European Journal of Sustainable Development, 2021)
Little is known about how social enterprises and social start-ups compete with the bigger players on the market. It could be reasoned that social start-ups gain an advantage by the deployment of Corporate Social Responsibility (CSR) elements from the early beginning as a part of their core competences. The aim of this paper is to investigate if CSR elements can be a core competence and how they can contribute to the robustness of the business models of social start-ups. Data was gathered by conducting a case study and interviewing four social entrepreneurs in the first half of 2017. The data was analyzed with the help of a framework built upon the CSR pyramid, the business case for CSR and the Canvas business model. The main findings show that the CSR elements economic, ethical and discretionary responsibilities can be a core competence for social start-ups. Moreover, CSR elements can play an important role in the design of social business models. Especially the deployment of interrelationships between the CSR elements seems to be effective in designing a robust business model of a social start-up.